International Tuberculum Sellae Meningioma Study: Surgical Outcomes and Management Trends. (16th November 2020) - Magill, Stephen T; Schwartz, Theodore H; Couldwell, William T; Gardner, Paul A; Heilman, Carl B; Sen, Chandra N; Akagami, Ryojo; Cappabianca, Paolo; Prevedello, Daniel M; McDermott, Michael W; ,
Abstract: INTRODUCTION: Tuberculum sellae meningiomas (TSM) can be resected via transcranial (TCA) or transsphenoidal (TSA) approaches, but comparative outcomes data is limited. METHODS: We conducted a 40-site retrospective study using standard statistical methods. RESULTS: Of 947 cases, a TCA was used in 629 (66.4%), a TSA in 318 (33.6%). Use of TSA has increased from 2003–2019 and is currently used in 50% of cases. Median max diameter was larger for TCA (2.5 cm, range 0.3-6.8 cm) compared to TSA (2.1 cm, range 0.3-5.1) ( P  < .0001). Median follow up was 26 months (0-265 months), and 63 (6.6%) were WHO grade II/III. Gross total resection (GTR) was achieved in 70.0% of cases and did not differ between TSA (68.2%) and TCA (71.2%) (OR 1.2 for TCA, 95%CI 0.9-1.5, p = 0.3667). On multivariate analysis (MVA), WHO II/III (OR 2.8, 95%CI 1.4-5.4) and TCA (OR 1.8, 95%CI 1.08-3.07) were associated with worse vision post-operatively, while GTR was protective (OR 0.4, 95%CI 0.2-0.6). On MVA, GTR was less likely in tumors with greater maximum diameter (OR 0.8 per cm, 95%CI 0.7-0.9) and those with pre-operative visual deficit (OR 0.6, 95%CI 0.4-0.9). Mortality was 0.5%. Complications occurred in 23.9%. New unilateral or bilateral blindness occurred in 3.3% and 0.4%, respectively. CSF leak rate was stable from 2007–2019, at 17.3% for TSA and 2.2% for TCA (OR 9.1, 95%CI 5.0-16.8). The recurrence rate was 10.8% (n = 103, 5-year freedom from recurrence: 84.2%). NTR/STR (OR 2.8, 95%CI 1.9-4.4) and WHO II/III (OR 2.6, 95%CI 1.4-5.1) were associated with increased recurrence, while older age (OR 0.96/year, 95%CI 0.94-0.98) was associated with decreased recurrence on MVA. After NTR/STR, there was no difference in recurrence rate between TCA and TSA, but the recurrence rate after GTR was lower after TSA compared to TCA (OR 0.3, 95%CI 0.1-0.7). CONCLUSION: The use of TSA for TSM is increasing and is associated with better visual outcomes and decreased recurrence rates after GTR. However, CSF leak rates after TSA remain high. These data support the use of TSA in appropriately selected patients where a GTR can be achieved.